Discussion of “Relating Product Prices to Long‐Run Marginal Cost: Evidence from Solar Photovoltaic Modules” - Parsons, John E. (Contemporary Accounting Research, 2018)
Abstract My discussion of Reichelstein and Sahoo (2018) is organized into three parts. First, what is the context for this work? That is, what are the energy and climate stakes? Second, what does the paper do? I will re‐work the equation defining the components of long‐run marginal cost to better reflect what is actually estimated and to better highlight some important choices about how the different components are modeled. Third, and most importantly, how do the results inform business decisions and policy choices regarding energy and climate? What more do we need?